2020
DOI: 10.1111/pce.13837
|View full text |Cite
|
Sign up to set email alerts
|

Coupled plant traits adapted to wetting/drying cycles of substrates co‐define niche multidimensionality

Abstract: Theories attempting to explain species coexistence in plant communities have argued in favour of species' capacities to occupy a multidimensional niche with spatial, temporal and biotic axes. We used the concept of hydrological niche segregation to learn how ecological niches are structured both spatially and temporally and whether small scale humidity gradients between adjacent niches are the main factor explaining water partitioning among tree species in a highly water‐limited semiarid forest ecosystem. By c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…Zhao et al (2016) also observed intratree fractionation of deuterium between water pools. The trunk and leaves of the oaks at our study site shrink and swell diurnally, due, presumably, to short‐term water storage and release (Hahm et al, 2018), as also recently observed in oak trunks studied by Rodríguez‐Robles et al (2020). It is possible that the roots also similarly store and release water, perhaps to the surrounding materials in the subsurface; if this water is isotopically altered within the plant it could then impart a distinct isotopic signature on the soil and weathered bedrock adjacent to roots, as well as the plant transpiration stream.…”
Section: Discussionsupporting
confidence: 82%
“…Zhao et al (2016) also observed intratree fractionation of deuterium between water pools. The trunk and leaves of the oaks at our study site shrink and swell diurnally, due, presumably, to short‐term water storage and release (Hahm et al, 2018), as also recently observed in oak trunks studied by Rodríguez‐Robles et al (2020). It is possible that the roots also similarly store and release water, perhaps to the surrounding materials in the subsurface; if this water is isotopically altered within the plant it could then impart a distinct isotopic signature on the soil and weathered bedrock adjacent to roots, as well as the plant transpiration stream.…”
Section: Discussionsupporting
confidence: 82%
“…7a). This fits the concept of hydrological niche segregation (Araya et al ., 2011), where co‐existing plants occupy different temporal and spatial niches under moderate drought conditions and do not necessarily compete strongly for water resources so long as water reserves are sufficient (Rodríguez‐Robles et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This result is supported by prior evidence for phylogenetic signals in root traits that may carry implications for RWU (Comas & Eissenstat, 2009; McCormack et al., 2020; Valverde‐Barrantes et al., 2017). Some ecosystems show evidence of seasonal oscillations between niche segregation and direct competition driven by seasonal soil water limitation (Andrews et al., 2012; De Deurwaerder et al., 2018; Kulmatiski et al., 2020; McCormack et al., 2020; Rodríguez‐Robles et al., 2020), suggesting higher‐order interactions between the phylogenetic, niche, and locality hypotheses. In a mixed species forests, co‐occurring trees may rely on similar water sources during dry days, but exhibit divergent RWU depths in response to recent precipitation (Grossiord et al., 2017; Liu et al., 2019; Volkmann et al., 2016).…”
Section: Discussionmentioning
confidence: 99%